Konsep Gharar Dalam Transaksi Modern Dan Implikasinya Terhadap Keabsahan Akad - Nur Amelia; Mohd Winario; Zubaidah Assyifa (Journal of Economic, Management, Business, Accounting Sustainability, 2026)
This study aims to analyze the concept of gharar in modern transactions and its implications for the validity of contracts from an Islamic legal perspective. Technological developments and economic digitalization have given rise to various new forms of transactions, such as e-commerce, fintech, digital investment, and online trading, which potentially contain elements of ambiguity, speculation, and uncertainty. This situation necessitates a reexamination of the application of the concept of gharar in contemporary muamalah practices. The research method used is qualitative research with a library research approach. Data were obtained through a review of classical fiqh literature, scientific journals, books, fatwas of scholars, and previous research related to gharar and modern transactions. The results show that elements of gharar are still prevalent in various modern transactions, especially those with unclear objects, prices, contract mechanisms, and high risks. This study also found that the dominant presence of gharar can render a contract invalid because it contradicts the principles of justice, transparency, and willingness in Islamic law. Therefore, a comprehensive understanding of sharia principles in modern transaction practices is necessary.